Treatment Objectives of a Patient with Severe Maxillary and Mandibular Crowding, Mandibular Retrognathia and Maxillary Prognathia - Fundagül Bilgiç; Güvenç Başaran; Pamir Meriç; Orhan Hamamcı (Galenos Yayinevi, 2012)
The purpose of this study was to evaluate the skeletal, dental and soft tissue changes in patient with severe maxillary and mandibular crowding, mandibular retrognathia and maxillary prognathia treated with four first premolar extraction and fixed functional treatment.